What Works and for Whom? Outcome Evaluation of an E-mail Walking Program Delivered Through Cooperative Extension - Elizabeth A. Richards; Stephanie Woodcox; Anna Forster (SAGE Publishing, 2022)
Introduction: Get WalkIN' is a 12-week, e-mail-based walking promotion program. The purpose of this study was to (1) compare sociodemographics of participants who enrolled versus completed the program; and (2) evaluate program feasibility/acceptability from perspectives of program participants and county-based Extension Educators who implemented the program. Methods: Participants (N = 875), recruited by county-based Extension Educators, were asked Likert-scale questions (eg, ease of reading the e-mails and frequency of e-mails) to assess program acceptability and open-ended questions regarding improvements. Educators (N = 55) were asked Likert-scale and open-ended questions regarding program training, recruitment, strengths, and areas for improvement. Descriptive statistics summarized participant characteristics, acceptability, and feasibility data. Open-ended responses were analyzed using thematic analysis. Results: There were no significant sociodemographic differences between participants (N = 875) who started the program and completed the program (n = 438). Participants reported intervention e-mails were easy to read (mean = 4.5 ± 0.7), understand (mean = 4.5 ± 0.7), and encouraged more walking (mean = 4.1 ± 0.9). Participants would like to connect/interact with other participants/Educators, have more monitoring tools for accountability, and more visuals/videos embedded within e-mails. Educators reported program training was adequate, e-mail messages were helpful and easy to use, and requested more visuals (eg, videos) to help with recruitment. Educators thought adding a social component (eg, kick-off walk or walking group) would be helpful. Conclusions: This Extension-delivered walking program is acceptable to participants and feasible to deliver. However, participants and Educators reported they would like more interaction, even if virtual. Future e-mail-based programs should consider ways to incorporate social interaction among users as well as provide a wide variety of recruitment resources.